In vitro experiment and computational fluid dynamics simulation study on blood pump for total cavopulmonary connection circulation - Wu, Yong; Chen, Tong; Cai, Yunhan; Wang, Shengzhang; Lu, Haiyan (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveThis study aimed to address the compromised hemodynamics in patients with total cavopulmonary connection circulation after Fontan surgery. While the Fontan procedure effectively separates systemic and pulmonary venous blood, resolving organ hypoxia, patients often experience complications such as elevated central venous pressure and reduced pulmonary artery pressure (Fontan failure) due to insufficient circulatory support. To improve this, a right ventricular assist device with a flexible impeller was designed. This study investigated the impeller’s characteristics through in vitro experiments and computational fluid dynamics (CFD) simulations, validating the accuracy and effectiveness of the CFD simulation method.MethodsThe study employed in vitro hydraulic experiments and particle image velocimetry (PIV) to test the hydraulic performance and flow field of the blood pump. Simultaneously, a simulation model was established, and CFD simulations were performed. By quantitatively comparing simulation and experimental results, pulmonary artery blood flow, increased central venous pressure, and the velocity field in the mid-plane of the left pulmonary artery during impeller rotation were evaluated. The experimental setup was designed to mimic physiological dimensions, ensuring consistency with real-world applications.ResultsThe results demonstrated that the simulation method accurately predicted the trends of various indicators, with maximum errors within acceptable limits. Specifically, the relative error between simulation and experiment for pulmonary artery outflow was a maximum of 1.65%. The relative error for elevated central venous pressure was small, except for a few points. The simulation results of the velocity field also accurately reflected the main characteristics observed in the experiments.ConclusionThis study validated the potential of the designed impeller in improving hemodynamics in patients after Fontan surgery through in vitro experiments and CFD simulations. The high consistency between simulation results and experimental data confirms the effectiveness of the CFD simulation method, laying the foundation for further optimization of blood pump performance.